Bits and bytes of financial regulation: the RegTech environment - Miguel, A. F. (2019)
Since 2008, banks have spent more than €342 billion on settlements, enforcement actions, and fines, and until 2020 according to Reuters this value is expected to rise to €400 billion. As a result, technological solutions were implemented to help financial institutions deal with the increasing compliance burden and regulators addressing the constant difficulties of enforcing and monitoring regulatory requirements to limit risks and promote financial stability. This led to the emergence of a whole new movement in the Financial Industry: Regulatory Technology or Regtech. The aim of this paper is to explain the regtech environment in the financial sector. We highlight how technology can help financial institutions dealing with risky behavior and regulatory demands in the most efficient and cost-effective way.